EFFECT OF BLOCKCHAIN ON ACCOUNTING INFORMATION SECURITY - Sincharoonsak, Titaporn; Nakavisute, Isara (Journal of MCU Nakhondhat, 2020)
Applying the online technology to the accounting work has been carried out continuously and has been seen more clearly. When the online technology such as Cloud Technology is used and applied with the accounting system, it has made the accounting work fast. Preparing financial statement consists of statements of financial position, statements of comprehensive income, statements of changes in shareholders’ equity, statements of cash flow and notes to financial statements. Applying the online technology to the accounting work is necessary and create benefits such as conducting and saving the financial transaction in real time, increasing the work performance and reducing the back office overhead cost. However the drawback of using cloud technology with accounting work is that the accounting data is public and can be used by a person whose intention is not good. It can create damage to the company. Blockchain technology is the technology which creates the data security. Conducting the online transaction can be completed conveniently and fast. Blockchain technology is the database management system and is linked to the accounting work including user authentication, financial transaction preparation and asset ownership recording. Account data security is important. Applying the blockchain technology to the cloud technology helps creating the confidence to the user that the accounting data will be kept confidential and safe. It will create credibility, transparency, accuracy, auditing system, global auditing network, reduced auditing time, less data error, zero risk for document forging and reduced corruption with the data being undeletable or unmodifiable in order to create the confidence to the financial statement users, especially the investors who will use such information to make the investing decision.